Pendampingan Produksi Sambal Terasi Kemasan Oleh Kelompok Wanita Tani Sari Asih Klirong - Ida Betanursanti; Galih Mahardika Munandar; Muhammad Nur Wahyu Hidayat; Alifta Dicasani (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
This community service aims to assist in the production process of packaged shrimp paste chili sauce for the Sari Asih Women Farmers Group (KWT) in Klegenwonosari village, Klirong sub-district. Making shrimp chili paste will be able to meet the availability of chilies throughout the year for daily consumption. The method implemented is assistance starting from planning, preparating the ingredients, treatments of chili ingredients before making chili sauce, the shrimp chili paste-making process, frying, packaging, and labeling. At each stage of the production process, insight into hygiene and health risks is providing so that packaged chili products are attractive with color, taste, and aroma that remain stable and safe for consumption. The accompanying production process of packaged shrimp paste chili sauce is starting from the preparation, manufacturing, and packaging processes. The preparation selects goods and fresh ingredients free from chemical and biological contaminants. The stage of making chili paste is to control the water and cooking oil content in the chili sauce to extend the shelf life. The packaging process involves selecting packaging made from polypropylene for safety, controlling water content, and closing the packaging tightly to extend shelf life.